A Comprehensive Literature Review of Surgical Management of Rotator Cuff Injuries - Indra Hadi Rapmartua Ompusunggu; Wahyu Agus (The Indonesian Journal of General Medicine, 2024)
Background: The surgical management of rotator cuff injuries has evolved significantly over the past few decades, with numerous studies exploring various techniques and their efficacy. The early work by Hopstad (Hopstad, 1998) highlighted the importance of postoperative pain relief and the integrity of the rotator cuff in determining functional outcomes.  Literature Review: Early studies, such as those by (Hopstad, 1998) and (J. Kohns, 2000), established that while the size of the tear is important, the integrity of the repair is a more critical determinant of functional success. Kohns further emphasized the importance of early surgical intervention and the role of physical therapists in optimizing outcomes. Recent innovations, such as tissue engineering approaches discussed by (Maffulli et al., 2012), aim to address the limitations of natural healing, suggesting biomechanical strategies to enhance tendon repair. (French, 2018) explored the kinematic assessments of the thoracohumeral joint, revealing that intraoperative factors and postoperative rehabilitation compliance significantly impact recovery. (Emmanuel, 2018) examined surgical options for young, active patients with irreparable rotator cuff tears, advocating for tailored interventions based on demographic characteristics. (Kim et al., 2020) summarized current surgical options for patients with failed rotator cuff repairs, emphasizing the necessity of understanding which patients may benefit from revision surgery. Conclusion: In conclusion, the body of literature collectively underscores the importance of understanding the multifactorial nature of rotator cuff injuries and their surgical management. Factors such as repair integrity, timing of intervention, patient demographics, and rehabilitation strategies are critical in determining outcomes. Continued research and innovation are essential to refine surgical techniques and improve recovery for patients suffering from rotator cuff injuries.